(untitled) (Journal of Pakistan Orthopaedic Association, 2022)
Knee Osteoarthritis affects millions of people around the world. Although joint replacement for end stage osteoarthritis improves the quality of life of many it is expensive and some people may not be satisfied with this procedure. However, concerns regarding conservative treatment of patients with early- to end-stage osteoarthritis is mounting. The usual conservative treatment options available for early- to moderate-stage osteoarthritis are anti-inflammatory drugs, steroids and hyaluronic acid injections, Ozone and prolotherapy. Evidence suggests that all such treatment have their own merit and demerits and none is safe in the long term. Due to potential side effects of the available treatment options, it is believed that regenerative medicine (stem cells and platelet rich plasma) can be a good alternative with better long-term outcome and minimal side effects for all stages of osteoarthritis. Regenerative medicine is the new treatment on the horizon that promises to enhances the healing process of damaged tissues and organs with or without the need of surgery and has better efficacy and safety profile.